Continuous Integration (CI) with Jenkins : learn about the technology and processes that speed-up quality assured software development - Bowersox, Kevin (O'Reilly Media, 2017)
"The Jenkins server or CI (continuous integration) server is a tool that allows software developers to automate many of the common tasks (testing, compiling, etc.) associated with software development. It's become a widely used software development technology (133 thousand active installs, 1 million+ users), because of its ability to dramatically speed up development while assuring code quality. This course teaches you the basics of using the Jenkins server, while explaining the core concepts that govern software automation: Continuous integration, continuous deployment, and continuous delivery."--Resource description page.